Betraying a generation how education is failing young people - Ainley, Patrick (Policy Press shorts, 2023)
From primary to post-graduate schools Patrick Ainley explains how English education is now driven by the economy and politics. Addressed to teachers and students at all levels of learning, it concludes by suggesting how we can begin to contribute towards a more meaningful and productive society